Creating tangible and intangible hospitality products with a sustainable value – The case of the Altes Land apples. Issue 1 (2nd January 2016) - Depke, Sofie-Charlotte; Lück, Christina; Peters, Jennifer; Wellmer, Lara; Seidel, Sarah
Abstract : This paper focuses on a specific sub-part of hospitality, namely sustainable product creation via regional integration. According to the research question "To what extent does the integration of local apple products contribute to regional sustainable value creation in Altes Land in regard to tourism stakeholders?" this research examined the sustainable value – defined as people, planet, profit – created by one specific regional food speciality, the apples of Altes Land. The region Altes Land, situated close to Hamburg, Germany, is known for its apple products and promotes them as part of the cultural heritage of the region. For this purpose, the concepts were defined as regional value creation, sustainable value creation and regional food products. The primary research was conducted in the form of thirteen interviews with farmers, inhabitants and domestic visitors. In addition, observation was conducted in the area with a focus on the farms. The outcomes of the research highlight multiple values created, where all the different types of interviewees perceived values on all three levels. The apples and their production are seen as both of a high cultural value and also as making an economic and environmental contribution to the region. In economic terms, both visitors and inhabitants are also willing to pay more and specifically look out for these apples when shopping, hence a special value is also attached to them.